PENINGKATAN KEMAMPUAN MEMBACA DAN MENULIS PERMULAAN MENGGUNAKAN STRATEGI BENGKEL LITERASI PADA SISWA SD - Nugraheti Sismulyasih Sb (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2018)
One of the studies that revealed the lack of students' reading ability, in this case the third grade students of SD/MI, is a Progress in International Reading Literacy Study (PIRLS) study, which is an international study on children's world-wide reading sponsorship sponsored by The International Association for the Evaluation Achievement. The study results show that the average Indonesian child is ranked fourth from bottom of 45 countries in the world. This makes the researchers trying to explain how the level of understanding of literacy in elementary school students and has the potential to improve the ability to read writing writing, especially in SD Labschool Kecamatan Gajahmungkur. The researcher uses a literary workshop strategy model to improve students' reading ability to write SD Labschool Kecamatan Gajahmungkur. The method used in this research is quasi-experimental method with one group pretest-posttest design. This research technique using 1) Test and 2)nontes (questionnaire, observation, and strategy of literary workshop). This research was conducted in Grade 3 of SD Labschool Kecamatan Gajahmungkur. The results of this study are the initial reading ability to write the beginning of 40% to 93.33% and unfinished from 60% to 6.67%, which means reading the beginning writingwith RW for elementary students is effective to improve understanding of reading ability.